Implementation of Profile Matching Method in Assessment of Employee Performance in Directorate General of Oil and Gas - Anggi Oktaviani; Jannes Parulian Siregar; Dahlia Sarkawi; Deny Novianti (Kresnamedia Publisher, 2020)
Every employee is always trying to improve their skills and achievements. So he can get a good career path according to his idea. Institutional Directorate General of Oil and Gas in the Ministry of ENERGY and Mineral Resources, as well as the assessment of employee performance also provided by the company to reward certain achievements. At this time analysis of assessment officers in Ditjen Migas is still done in a subjective. There should be ways and methods as an alternative election leader to suit your needs. In this study, the profile matching method was used as an alternative to providing assessment and evaluation of the key performance indexes of each employee. There are two aspects in conducting assessment and evaluation, namely: the performance aspect and the work satisfaction aspect. There are several levels of performance aspects: leadership of thoroughness and responsibility, verbalization of ideas, encouragement of achievement, concentration, and creative imagination. The work satisfaction aspect has discipline, high moral values, skills, integrity, and loyalty. There is a ranking change from candidates after being counted by the profile matching method whose employees with NIP 1388510026 have the first position in 4.5137.